Francis Bacon - Sylvester, David (New York : Pantheon Books, 1975)
On March 19, 1975, the Metropolitan Museum of Art in New York opened a major retrospective exhibition of Francis Bacon's work, an extremely rare distinction for a living painter. The show has focused renewed attention on one of the twentieth century's greatest artists and England's leading painter. Over a period of twelve years, from 1962 until 1974, the distinguished art critic David Sylvester conducted a series of extraordinarily revealing interviews with Francis Bacon. From the transcripts of these encounters was drawn this unusual book, which amounts to a statement by Bacon on his work and on art in general. Bacon is highly articulate about his aims as a painter and the ways in which he works, and about his life, responding always with vivacity and candor to Sylvester's searching questions. Bacon's obsessive effort to record and re-create the human form, his practice of making variations on old masters' paintings and on photographs, his dependence upon chance, his ideas for making sculptures, his views about the way his work has been interpreted, are only some of the subjects investigated in depth during these encounters. Few modern artists have ever spoken so openly about their work. In doing so, Francis Bacon tells us much more than one could have expected. This is a fascinating book not only about Bacon's work, but about the process of art itself.
Engels
boek
Keywords: Bacon, Francis